Politik Hukum Pembentukan dan Penerapan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Ramadhani, Indiyastuti (Universitas Ekasakti, 2023)
This research discusses the role of legal politics in the formation and implementation of Law Number 11 of 2008 concerning Information and Electronic Transactions. The author's research focuses on how politics in law is used as a background and influences the government in issuing the Information and Electronic Transactions Law. In preparing this research, the author also discussed the role of legal politics in dealing with various problems in the implementation of the Information and Electronic Transactions Law through various decisions and coordination between law enforcement agencies and related ministries. The results of this research show that the formation, drafting and publication of the Information and Electronic Transactions Law was greatly influenced by the legal politics that existed at that time and that various problems in its implementation could be mitigated by an agreement between the police, prosecutor's office and the ministry in the field of communications and informatics through a joint decision letter in the context of enforcing criminal articles regulated in the Information and Electronic Transactions Law.